Benzo[1, 2, 5]thiadiazole dyes: Spectral and electrochemical properties and their relation to the photovoltaic characteristics of the dye-sensitized solar cells. (September 2017) - Grishina, Maria; Bol'shakov, Oleg; Potemkin, Andrey; Potemkin, Vladimir
Abstract: Important aspects of dye-sensitized solar cells (DSSCs) fabrication based on dyes including benzothiadiazole unit were investigated. Two absorption peaks of the dyes covering the 330–551 nm region and possessing moderate band energy gap (1.83–2.16 eV) were found to be important to demonstrate high photovoltaic efficiency ( η  > 8) in metal free iodide/iodine electrolyte composed DSSCs. Furthermore, the dye energy band gap determined from optical spectra decreases with the increase of DSSCs short circuit photocurrent density, which in turn linearly increases the photovoltaic efficiency of DSSCs. While the RedOx potentials of dyes are less functionally related to the photovoltaic properties of the DSSCs, their appropriate values (0.67 ≤  E ox  ≤ 1.1 V and −1.75 ≤  E red  ≤ −0.91 V) can be important for efficient DSSCs. Fabrication details increasing photovoltaic efficiency of the devices based on dyes with benzothiadiazole unit were found. The relationships obtained in the work can be used for preliminary prognosis whether a newly synthesized dye is a promising metal-free sensitizer for DSSCs or not. Highlights: Efficiency of DSSCs with benzothiadiazole unit containing dyes correlates with Jsc. The dyes of high efficient DSSCs possess absorption peaks covering 330–551 nm region. Spectrally obtained dye band energy gap correlates with Jsc of DSSCs. Dyes RedOx properties do not correlate with the DSSCs photovoltaic performances.